Knowledge attitude assessment regarding fire safety among healthcare workers in tertiary care teaching hospitals in the eastern region of India - Mondal, Ramkrishna; Sinha, Sujeet Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Fire in any occupancy has the potential to cause harm to its occupants and severe property damage. Fire accidents in hospitals can lead to many injuries and death. Knowledge and practices of healthcare workers about fire safety prevention can save many lives. The objective was to assess the knowledge and attitude level on fire safety among healthcare workers in tertiary care teaching hospitals in the eastern region of India. Methods: In this cross-sectional study, 500 pre-tested questionnaires from four distinct sets were delivered to five categories of healthcare workers to prevent bias, and 424 responses were gathered as a fully voluntary activity, with a 84.4% response rate. Each questionnaire contains two sections that assess respondents’ knowledge and attitudes. MS Excel was used to analyze the data, along with simple statistical tests. Results: The analysis of healthcare professionals’ knowledge and attitude towards fire safety revealed an average total score of 5.75±1.66, with a knowledge score of 2.59±1.22 and an attitude score of 3.16±0.92. Among healthcare workers, doctors had the highest knowledge score (3±1.25) while others had the lowest (2.22±1.13). The doctor had the highest attitude level (3.33±0.67), while the security group had the lowest. The doctor group scored the highest (6.33±1.56), while the security group scored the lowest (5.34±1.69). Conclusions: The majority of healthcare workers in the study setup had significant knowledge but still considering the important role of every employee in fire accidents there is an important need to give fire safety training for all healthcare workers in timely intervals.